Novos registros georeferenciados de Tityus serrulatus Lutz & Mello, 1922 (Scorpiones, Buthidae) para o estado do Mato Grosso, centro-oeste do Brasil - Ribeiro Junior, Jessé M.; Pazóti, Pablo M.; Schneider, Marielle C.; Carvalho, Marcos A.; Strüssmann, Christine (Entomological Communications, 2025)
We present additional records of Tityus serrulatus Lutz & Mello, 1922 (Scorpiones: Buthidae) for the state of Mato Grosso, midwestern Brazil. The record of this scorpion species, which can cause mild to severe envenomation, significantly contributes to the knowledge of scorpionism in the state, as well as to the mapping of its distribution in the Brazilian territory. A morphologically similar species is abundant in the area - Tityus confluens Borelli, 1899 (Scorpiones: Buthidae), also presenting a general uniform yellow coloration - but is usually responsible for less severe scorpion accidents. The correct identification of both species by health agents and the general population may be relevant for the appropriate treatment of local scorpion sting cases.